2002
DOI: 10.1074/jbc.m111246200
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Prostaglandin E2 Synthesis by Interleukin-1β in Human Orbital Fibroblasts Involves Coordinate Induction of Prostaglandin-Endoperoxide H Synthase-2 and Glutathione-dependent Prostaglandin E2 Synthase Expression

Abstract: Prostaglandin E 2 (PGE 2 ) production involves the activity of a multistep biosynthetic pathway. The terminal components of this cascade, two PGE 2 synthases (PGES), have very recently been identified as glutathionedependent proteins. cPGES is cytoplasmic, apparently identical to the hsp90 chaperone, p23, and associates functionally with prostaglandin-endoperoxide H synthase-1 (PGHS-1), the constitutive cyclooxygenase. A second synthase, designated mPGES, is microsomal and can be regulated. Here we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
117
1
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 45 publications
14
117
1
2
Order By: Relevance
“…The effect was intermediate at a cytokine concentration of 5 ng/ml and was near-maximal at 10 ng/ml. Thus, the dose dependency is consistent with other established actions of IL-1␤ in orbital fibroblasts (32).…”
Section: Il-1␤ Up-regulates the Expression Of Il-6 Protein From Orbitsupporting
confidence: 89%
See 2 more Smart Citations
“…The effect was intermediate at a cytokine concentration of 5 ng/ml and was near-maximal at 10 ng/ml. Thus, the dose dependency is consistent with other established actions of IL-1␤ in orbital fibroblasts (32).…”
Section: Il-1␤ Up-regulates the Expression Of Il-6 Protein From Orbitsupporting
confidence: 89%
“…Several of these inductions are mediated through the activation of p38 and ERK 1/2 MAPK pathways (32). Treatment with IL-1␤ (10 ng/ml) resulted in the very rapid phosphorylation of p38 (Fig.…”
Section: Induction Of Il-6 By Il-1␤ Uses the P38 And Erk Mapk Pathwaysmentioning
confidence: 97%
See 1 more Smart Citation
“…Cytokines and lipid mediators, synthesized by infiltrating T lymphocytes, monocytes, and mast cells, drive tissue remodeling, including the accumulation of hyaluronan, an abundant nonsulfated glycosaminoglycan (25,26). The unique phenotype of orbital fibroblasts and their exaggerated responses to cytokines such as IL-1␤ represent the basis for disease susceptibility of these tissues (25,(27)(28)(29)(30)(31). Why immunocompetent cells are recruited to the orbit in TAO remains uncertain.…”
mentioning
confidence: 99%
“…A recent gene targeting study of mPGES-1 has shown that PGE 2 production by lipopolysaccharide-stimulated peritoneal macrophages depends almost entirely on this enzyme (29). Induced expression of mPGES-1 is regulated by the NF-IL-6 pathway (29) or the mitogen-activated protein kinase pathway (30), the latter of * This work was supported by a Showa University grant-in-aid for Innovative Collaborative Research Projects and a Special Research grant-in-aid for Development of Characteristic Education from the Japanese Ministry of Education, Culture, Sports, Science and Technology of Japan. The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 99%